2013
DOI: 10.1177/2048872613475891
|View full text |Cite
|
Sign up to set email alerts
|

Impaired coronary microvascular reactivity in women with apical ballooning syndrome (Takotsubo/stress cardiomyopathy)

Abstract: Aims: The pathophysiology of apical ballooning syndrome (ABS) remains to be elucidated. The aim of this study was to evaluate the coronary vascular reactivity of patients who were previously diagnosed with ABS. Methods and results: A total of 228 cases of ABS were prospectively identified, and of these, 10 patients (median age 61 years ; all females) who underwent coronary vasomotion testing were included in the study. Coronary epicardial and microvascular responses to intracoronary acetylcholine (ACH; % chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 19 publications
1
55
0
4
Order By: Relevance
“…Epicardial coronary artery vasospasm and consequently regionally stunned myocardium may induce reversible LV wall motion abnormalities (1). Several studies investigating vasospastic provocation in the acute phase of TTC demonstrated positive results (10-43%) but not in all TTC patients (4,20). Various studies have reported that the endothelin levels are higher in patients with TTC than those with AMI (21).…”
Section: Introductionmentioning
confidence: 95%
“…Epicardial coronary artery vasospasm and consequently regionally stunned myocardium may induce reversible LV wall motion abnormalities (1). Several studies investigating vasospastic provocation in the acute phase of TTC demonstrated positive results (10-43%) but not in all TTC patients (4,20). Various studies have reported that the endothelin levels are higher in patients with TTC than those with AMI (21).…”
Section: Introductionmentioning
confidence: 95%
“…Vasospastic provocation has been studied during the acute phase, with evidence in 10-43% patients in various series 58,59 . In non-Japanese populations, especially when performed in the convalescent phase or later, epicardial coronary vasospasm is not a common finding, whereas microvascular dysfunction was more common 60 . A review of 9 cohort studies concluded provocation-induced vasospasm was present in 34 of 123 patients studied (27.6%) 61 .…”
Section: Acute Multivessel Coronary Spasmmentioning
confidence: 99%
“…There is evidence for increased adrenergic activity with microvascular spasm and subsequent reduced or sluggish blood flow [6][7][8]. Reduced or impaired microvascular vasoreactivity has been measured in clinical studies where measurements are generally recorded in patients after the heart is already damaged.…”
Section: Editorialmentioning
confidence: 99%
“…We would like to open a discussion around the prevailing opinions and the available evidence that this cardiomyopathy is the result of an adrenaline surge, with stress causing microvascular dysfunction on a wide scale [6][7][8]. Atherosclerotic plaque rupture or erosion with in situ thrombosis resulting in ST elevation myocardial infarction (STEMI or acute heart attack) has been considered a distinct event, unrelated to Tako-tsubo cardiomyopathy.…”
Section: Editorialmentioning
confidence: 99%